COVID-associated pulmonary aspergillosis and azole resistance Aspergillus species; a laboratory-based study from Pakistan - Zaka, Sadaf; Shahid, Mehreen; Farooqi, Joveria; Raheem, Tooba; Naqvi, Muhammad Faheem; Jabeen, Kauser (Infectious Diseases Journal of Pakistan, 2025)
Background: COVID-19-associated pulmonary aspergillosis (CAPA) has emerged as a significant complication in critically ill patients, leading to increased morbidity and mortality, particularly when diagnosis is delayed or antifungal resistance is present. A previous study from our centre reported a CAPA incidence of 21.7% with high associated mortality. This study aimed to evaluate azole resistance in Aspergillus species isolated from COVID-19 patients using a standardized screening approach. Materials and Methods: This study included Aspergillus isolates recovered from respiratory specimens of COVID-19 patients admitted to Aga Khan University Hospital, Karachi, between July 2020 and January 2022. Azole resistance screening was performed using the CDC agar-based methodology with itraconazole, voriconazole, and posaconazole. Isolates that demonstrated growth in any azole-containing well were further tested for minimum inhibitory concentrations (MICs) using broth microdilution. Quality control strains included Candida parapsilosis ATCC 22019, Candida krusei ATCC 6258, and A. flavus ATCC 204304. Results: A total of 174 Aspergillus isolates (A. flavus 85, A. niger 41, A. fumigatus 36, A. terreus 8, A. nidulans 3, A. versicolor 1) from 125 patients (40 CAPA; 85 colonization) were analysed. Growth was observed on voriconazole screening agar in 24 (13.7%) isolates. No growth was seen in the itraconazole or posaconazole wells. MIC testing of 18 voriconazole-screened isolates confirmed that all were azole-susceptible. Conclusion: Although initial screening suggested possible azole resistance, none were confirmed resistant by MIC testing. These findings highlight the need for continued surveillance to monitor emerging resistance in Aspergillus species in Pakistan. Keywords: Azole resistance, CAPA, COVID-19